2014
DOI: 10.1186/1757-4749-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Detection, identification and quantification of Campylobacter jejuni, coli and lari in food matrices all at once using multiplex qPCR

Abstract: BackgroundThermotolerant Campylobacter jejuni, coli and lari are recognized as leading food-borne pathogens causing an acute bacterial enteritis worldwide. Due to narrow spectrum of their biochemical activity, it is very complicated to distinguish between individual species. For reliable risk assessment, proper incidence evaluation or swift sample analysis regarding individual species, a demand for simple and rapid method for their distinguishing is reasonable. In this study, we evaluated a reliable and simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In many research studies, multiplex PCR has been applied for rapid identification of diarrheal agents 25, 26. All of these studies noted that multiplex PCR is a reliable, useful, and cost-effective assay, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In many research studies, multiplex PCR has been applied for rapid identification of diarrheal agents 25, 26. All of these studies noted that multiplex PCR is a reliable, useful, and cost-effective assay, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…There are numerous transmission routes for Salmonellosis, but the majority of the human infections are derived from consumption of contaminated poultry products (Saha et al, 2016). Thermo-tolerant bacteria belonging to Campylobacter genus (especially C. jejuni, C. coli, C. lari and marginally C. upsaliensis) are recognized as leading human foodborne pathogens causing an acute gastrointestinal disease called campylobacteriosis ) Vondrakova et al, 2014).Chicken meat must be of a high microbiological quality in order to ensure that the consumer receives a product that is not spoilt, or does not carry foodborne disease.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter only (Wiemer et al, 2011;Buchan et al, 2013;Vondrakova et al, 2014). This is an advantage of this study as the listed Campylobacter species have been shown to cause a number of infections (EFSA, 2015a,b).…”
Section: Discussionmentioning
confidence: 98%
“…The qPCR assays which included the Campylobacter 16S rRNA gene rrna among targets, enabled to detect three Campylobacter species, namely C. jejuni , C. coli and C. lari in the multiplex conditions along with other foodborne pathogens in contrast to previously published multiplex detection systems developed for Campylobacter only (Wiemer et al ., ; Buchan et al ., ; Vondrakova et al ., ). This is an advantage of this study as the listed Campylobacter species have been shown to cause a number of infections (EFSA, ,b).…”
Section: Discussionmentioning
confidence: 99%